ANALISIS PORTOFOLIO OPTIMAL MENGGUNAKAN METODE LEXICOGRAPHIC GOAL PROGRAMMING DENGAN PENDEKATAN VaR – GEV - SERAN, YOHANA Th.V.; DHARMAWAN, KOMANG; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 11 No 2 (2022)DO - 10.24843/MTK.2022.v11.i02.p370, 2022)
The stock portfolio is a combination of several stocks that can help reduce investment risk. Risk can be measured using Value at Risk. This study aims to form an optimal portfolio in which stock risk is estimated using VaR with Generalized Extreme Value distribution followed by selecting the optimal portfolio forming stock using the Lexicographic Goal Programming method. The result of this research is that a portfolio with three selected stocks is formed, namely BBRI with a proportion of 63%, KLBF with a proportion of 25% and MNCN with a proportion of 12%. From the optimal portfolio formed, the expected return is 0.00005106 and the risk is 0.0187.